2012
DOI: 10.7314/apjcp.2012.13.8.3949
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Histopathological Spectrum of Head and Neck Cancers in Bihar, a State of Eastern India

Abstract: Head and neck cancers are amongst the commonest malignancies, accounting for approximately 20% of the cancer burden in India. The major risk factors are tobacco chewing, smoking and alcohol consumption, which from 2002-2006 at Patna Medical College and Hospital, a tertiary care hospital drawing patients from the entire Bihar state, the 3rd most populous state of India with the majority of the population residing in rural areas. Incidence rates based on sex, age, site of lesion, including age standardized incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 12 publications
5
29
0
Order By: Relevance
“…11 Our research study showed a preponderance of males in all three histopathological categories which was in accord with the findings of Siddiqui M S et al 15 A wide variety of lesions spanned across the seven topographic sites we analyzed. Lesions arising from the skin and the soft tissues were found to be maximum (29.65%) in present study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…11 Our research study showed a preponderance of males in all three histopathological categories which was in accord with the findings of Siddiqui M S et al 15 A wide variety of lesions spanned across the seven topographic sites we analyzed. Lesions arising from the skin and the soft tissues were found to be maximum (29.65%) in present study.…”
Section: Discussionsupporting
confidence: 79%
“…11,14 Oral squamous cell carcinoma was the commonest malignancy reported in our work which was also seen in studies done by other authors. 15,17,18 Lesions of the aero-digestive tract comprised of 17.24% cases in our data among which inflammatory lesions were the maximum followed by malignant. Inflammatory lesions included tonsillitis, adenoiditis and nasal polyps.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 Studies have shown that the usage of tobacco in various forms is mounting at the rate of 2 to 3% yearly, and it is expected to cause about 13% of deaths in India by 2020. 9 Oral cavity has rich blood supply and lymphatic drainage, therefore the likelihood of cervical metastases of OSCC is very high making it a life-threatening disease. 10 Hence, early diagnosis and treatment is necessary in oral cancer as studies have shown that a cure rate of over 90% can be achieved in early stages.…”
Section: Resultsmentioning
confidence: 99%
“…Oral cancer is a subtype of head and neck cancer is any cancerous tissue growth located in the oral cavity 1 . There are several types of oral cancers, but around 90 % are squamous cell carcinomas, originating in the tissues that line the mouth and lips and cheek lining 2 .…”
Section: Introductionmentioning
confidence: 99%